PREACH THE WORD: THE MEANING OF LOGOS IN 2 TIMOTHY 4:2 - Aguiar, Adenilton Tavares (Práxis Teológica, 2019)
The purpose of this paper is to suggest a solution to the following question: “What is the understanding that Timothy and the original audience have about the meaning of λόγος in the exhortation Preach the Word?”. The literature on this topic has offered several options: 1. Gospel; 2. Scripture; 3. More generic meanings such as sound doctrine, true faith, word of truth, and Paul’s teachings. This paper is divided into three parts. The first one aims to demonstrate that the recent debate points out, in synthesis, to either Gospel or Scripture as the meaning intended by Paul. The second one performs a brief analysis of λόγος throughout the New Testament. Finally, the third one assesses the text and the context of 2 Timothy 4:1-5 in order to verify the meaning of λόγος in such a passage. The data analyzed in this paper allow us to conclude that an inseparable unity between the Gospel and Scripture is the best option for the meaning of λόγος in 2 Timothy 4:2. Indeed, Paul uses this term to refer to the Christ-event just as it is described in the Old and New Testament, i.e., life, death, and resurrection of Jesus Christ. However, for Paul, the relationship between Scripture and the Christ-event – or vice versa – forms an inseparable unity, so that affirming that by the word λόγος he also meant Scripture is not a mistake